Do natural resource revenues lower government reliance on seigniorage? The role of exchange rate policy. (8th February 2018) - Ellis, Michael A.; Elbahnasawy, Nasr G.
Abstract: The study investigates how the degree of exchange rate management conditions the relationship between seigniorage and governments' natural resource revenues using a sample of 140 countries over the period from 1971 to 2012. It also disaggregates natural resource revenues to investigate if this relationship holds across the various types of natural resources. The main approach is to estimate dynamic panel data interaction models. The study finds that under exchange rate regimes characterized as fixed or of limited flexibility an increase in natural resource rents is associated with an increase in seigniorage. Under crawling currency bands and managed floating, an increase in natural resource rents has little association with seigniorage. Under exchange rate regimes permitting greater exchange rate flexibility, greater natural resource rents allow less reliance on seigniorage. Additionally, the direct relationship between natural resource rents and seigniorage is driven mostly by oil and natural gas.